Vacuolar Protein Sorting 33B Is a Tumor Suppressor in Hepatocarcinogenesis. Issue 6 (5th November 2018) - Wang, Conghui; Cheng, Yuqiang; Zhang, Xiuping; Li, Nan; Zhang, Lin; Wang, Shengdian; Tong, Xuemei; Xu, Ying; Chen, Guo‐qiang; Cheng, Shuqun; Fan, Xuemei; Liu, Junling
Abstract : Polarity defects are frequently involved in liver diseases, such as chronic hepatitis and hepatocellular carcinoma (HCC). It was reported that vacuolar protein sorting 33B (Vps33b) plays critical roles in the maintenance of hepatocyte polarity; however, the functional roles and mechanisms of Vps33b in HCC occurrence and progression remain unknown. First of all, we showed that Vps33b is down‐regulated in human and mouse liver cancer samples, and the low expression levels of Vps33b correlate with the poor prognosis of many HCC patients. Liver‐specific Vps33b deficiency induces liver damage, progressive hepatitis, fibrosis, and HCC in male mice, indicating that Vps33b is a crucial contributory factor to hepatocarcinogenesis. Vps33b deficiency–caused liver damage was primarily due to the disorders of structural and functional hepatocyte polarity, which were reflected by the decreased protein levels of E‐cadherin because of inaccurate location to lysosomes and polarity defects at both apical and lateral plasma membrane proteins. The results of a mechanism study revealed that Vps33b interacts with VPS33B‐interacting protein, which is involved in polarity and apical protein restriction; vesicle‐trafficking protein Sec22b; and Flotillin‐1 in hepatocytes and is in charge of the normal distribution of polarity‐determined proteins. Expression levels of Vps33b negatively correlated with the degree of inflammatory cell infiltration in livers from diethylnitrosamine‐induced or transgenic HCC mouse models, and the inflammatory stimuli suppressed the expression of Vps33b in vitro . Conclusion: Down‐regulation of Vps33b expression is a critical step for inflammation‐driven HCC, and Vps33b serves as an important tumor suppressor in hepatocarcinogenesis.